FUNGSI KELOMPOK TANI DAN PENGGUNAAN INPUT PRODUKSI DALAM KEGIATAN USAHATANI JAGUNG DI DESA MAPERAHA KECAMATAN SAWERIGADI KABUPATEN MUNA BARAT - Salun Salun; Anas Nikoyan; La Ode Kasno Arif (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This research aims to determine the function of farmer groups and the use of production inputs in corn farming activities in Maperaha Village, Sawerigadi District, West Muna Regency with a total of 14 informants. The method in this research uses qualitative analysis as proposed by B. Milles and Huberman 2014, namely data reduction, data presentation, and drawing conclusions. The results of the research show that the function of the farmer group is as a learning class, showing that the farmer group functions in formulating learning needs and holding meetings marked by active group members, as a vehicle for cooperation, showing that the farmer group is active in collaborating with fellow farmer group members, as a production unit shows that The group is active in providing agricultural production facilities, while the use of production inputs shows that in corn farming activities all production inputs are used by farmers in their farming activities.